Implementation of Competency-Based Training Policy to Improve Employee Performance at The North Nias Regency Health Office - Jentri Mei Putra Zalukhu; Meiman Hidayat Waruwu; Sukaaro Waruwu; Jeliswan Berkat Iman Jaya Gea (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study investigates the implementation of a competency-based training policy and its effect on employee performance at the Health Office of North Nias Regency. Using a qualitative descriptive approach, primary data were gathered through in-depth interviews, direct observation, and document review involving managerial and operational staff. Analysis followed an interactive model of data reduction, display, and conclusion drawing. Findings indicate that competency-based training has positively influenced technical skills, job knowledge, motivation, work discipline, task execution, and responsibility in public service delivery. Nevertheless, the implementation is constrained by limited training budgets, inadequate facilities and infrastructure, unequal training opportunities, insufficient post-training evaluation and follow-up, and heavy operational workloads that reduce training participation. The study concludes that competency-based training contributes to improved employee performance when supported by comprehensive planning, sufficient resources, systematic evaluation, and institutional commitment. Recommendations include strengthening budgetary allocations, upgrading training facilities, implementing structured post-training evaluation, and aligning training programs more closely with job-specific competency needs.